Circular economy engagement - Morais, Larissa Herminio Lopes de (2021)
Morais, L. H. L. D., Pinto, D. C., & Cruz-Jesus, F. (2021). Circular economy engagement: Altruism, status, and cultural orientation as drivers for sustainable consumption. Sustainable Production and Consumption, 27(July), 523-533. https://doi.org/10.1016/j.spc.2021.01.019